Investigation of Determinant Roots in The Absorption of Education Budget - Anggraeni, Neni; Indarto; Santoso, Aprih (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study aims to analyze the effect of budget planning, human resource competence, and budget execution on budget absorption with motivation as a mediating variable at State High School Sub-Rayon IV Semarang City. In this study, the sample was all employees related to budgeting at State Senior High Schools in Sub-Rayon IV Semarang City, totaling 64 respondents (census method). The analysis tools are 1) a validity test, 2) a reliability test. 3) classic assumption test (multicollinearity test). 4) heteroscedasticity test. 5) hypothesis testing (t and F). 6) intervening test (Sobel test). 7) test the coefficient of determination. 8) stepwise multiple regression analysis. The research results show that: 1) budget planning, human resource competence, and budget execution significantly and positively affect budget absorption. 2) budget planning, human resource competence, and budget execution significantly and positively affect motivation. 3) Motivation has a significant and positive effect on budget absorption. 4) motivation can mediate the effect of budget planning, human resource competence, and budget execution on budget absorption in State Senior High Schools in Sub-Rayon IV Semarang City. The research concludes that budget planning, human resource competency, and budget implementation affect motivation and budget absorption in SMA Negeri in Sub Rayon IV Semarang City. Keywords: planning, competence, budget, motivation, absorption